Tax policy and the financing of innovation - Bryce, Luis A.; Bonfatti, Roberto; Luigi, Pisano (Elsevier, 2016)
We study tax policy in a Schumpeterian growth model with asymmetric information in the financing of innovation. Investors cannot a priori distinguish between more or less talented entrepreneurs. Net-worth allows talented entrepreneurs to self-invest and avoid being pooled with less talented entrepreneurs in the credit market. Increasing net-worth boosts innovation even when financed through higher profit taxes. Taxing consumption effectively raises net-worth and subsidizes profits simultaneously. Sufficiently taxing consumption implements the social optimum free of adverse selection. If forced to tax consumption less, the government implements a second best allocation with adverse selection when boosting net-worth enough to avoid adverse selection requires taxing profits excessively.